1996
DOI: 10.1093/ije/25.4.791
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Lead Exposure and Blood Pressure

Abstract: The present study suggests that short-term lead exposure, either ambient lead exposure or blood lead level, was not related to blood pressure change among workers who had been exposed at work to occupational lead. These results add to the body of evidence indicating that blood lead exposure does not adversely affect blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 2 publications
1
23
1
Order By: Relevance
“…In a study of Boston police officers with levels somewhat higher than the current general population, there was a statistically significant association between a high (>30 µg/dl) blood lead level and subsequent elevation in systolic pressure after 5 yr. Two meta-analyses that examined the studies of blood lead and blood pressure are in agreement that there is a correlation between the two parameters, though the magnitude and clinical significance is debatable 2) . In addition, other studies 3,4) did not indicate any relationship between exposure to lead and blood pressure.…”
Section: Introductionmentioning
confidence: 81%
“…In a study of Boston police officers with levels somewhat higher than the current general population, there was a statistically significant association between a high (>30 µg/dl) blood lead level and subsequent elevation in systolic pressure after 5 yr. Two meta-analyses that examined the studies of blood lead and blood pressure are in agreement that there is a correlation between the two parameters, though the magnitude and clinical significance is debatable 2) . In addition, other studies 3,4) did not indicate any relationship between exposure to lead and blood pressure.…”
Section: Introductionmentioning
confidence: 81%
“…Blood lead determinations were performed at the Faculty of Science and Central Laboratories Unit, UAE University with a Philips PU 9100X (Byunikan) atomic absorption spectrophotometer (AAS) equipped with graphite furnace and Zeeman background correction system. The analytical method used followed that described by Wu et al (1996). All specimens were analyzed three times and the average was taken when the relative standard deviation was less than 5%.…”
Section: Analysis Of Blood Lead Concentrationsmentioning
confidence: 99%
“…In addition, signi®cant correlations between blood lead and a variety of risk factors for cardiovascular disease (CVD) such as hypertension (Wu et al 1996;Schwartz 1988;Weiss et al 1986), and diabetes mellitus (DM) have been well-established Hayashi et al 1999);Schwartz 1995;DeFronzo 1997;Bener et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…M ost, [1][2][3][4][5][6][7][8][9][10] but not all, [11][12][13][14][15][16] studies have indicated that environmental exposure to lead is associated with an increased risk of hypertension and renal disease. A strong association between blood lead level and prevalence of hypertension was noted in the Second National Health and Nutrition Examination Survey (NHANES II).…”
mentioning
confidence: 99%